The museum of Fine Arts of Asturias as an educational resource from a gender perspective - de la Fuente Martínez, Ángel (Avances en Supervisión Educativa, 2016)
The museum as an educational resource is a proposal to make teachers reflect on the availability of media in the near environment regardless of the distance from the school to the museum. This gallery can work the general objectives in different educational stages, knowing the enhancement of historic buildings for activities of this type, the key work skills and promote the presence of women within the museum as an icon through different themes and artist. Our goal is to recover in perspective the presence of women sharing the same space and time with the man. The analysis of the trades, real social division of labor that this prefixed men do, that women, allows us to better understand the evolution of society. On the other hand, the postponement of the woman as artist, being supplanted by other painters, see Sofonisba Anguissola, it is another area in which it affects this article. Finally, different museums in which the woman is the protagonist in our country as an initiative to regain the role that women have played throughout the spatial and temporal coordinates, which are defining the development of the actions listed beings humans.